Serum nonesterified fatty acids, ghrelin, and homocysteine levels in women with polycystic ovary syndrome - Temel, Ismail; Celik, Oender; Hascalik, Seyma; Celik, Niluefer; Sahin, Ibrahim; Aydin, Sueleyman (Tubitak Scientific & Technological Research Council Turkey, 2010)
Aim: To investigate the possible relationship of serum levels of nonesterified fatty acids (NEFA), ghrelin, and homocysteine levels to metabolic and hormonal features in women with polycystic ovary syndrome (PCOS). Materials and methods: Thirty women with PCOS and 30 healthy women with similar age and body mass index (BM I) were recruited. Fasting serum NEFA, ghrelin, homocysteine, growth hormone (GH), cardiac troponin I, glucose, insulin, lipids, and homeostasis model assessment of insulin resistance (HOMA-IR) were measured. Results: Serum NEFA, homocysteine, insulin, HOMA-IR, cholesterol, and testosterone levels were significantly higher but in contrast ghrelin level was significantly lower in women with PCOS compared to the controls. No significant differences were found in the troponin I and GH levels between the 2 groups. Significant positive correlations between insulin-NEFA and insulin-homocysteine levels were observed. There was no significant correlation between ghrelin-insulin and ghrelin-homocysteine levels. Conclusion: The decreased ghrelin, elevated NEFA and homocysteine levels, and the correlation of NEFA and homocysteine to fasting insulin level might play an important role in the pathogenesis of the PCOS. These findings need to be confirmed and larger prospective and controlled studies are necessary.
Polikistik over sendromlu kadınlarda serum nonesterifiye ya? asitleri, grelin ve homosistein düzeyleri
Keywords: NEFA; ghrelin; homocysteine; insulin; PCOS